Perilaku Golongan Putih Masyarakat Kota Tanjungbalai Kecamatan Sei Tualang Raso Pada Pemilihan Kepala Daerah Gubernur Sumatera Utara Tahun 2018 - Murni Murni; Cut Maya Aprita Sari (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2019)
AbstrakKecamatan Sei Tualang Raso memiliki tingkat Golongan Putih yang lebih tinggi dibandingkan dengan Kecamatan lainnya sebesar 44,5% .Masyarakat Kecamatan Sei Tualang Raso memiliki pendidikan yang cukup tinggi dan berpengetahuan tentang politik yang cukup. pikir.Namun faktanya masyarakat Kecamatan Sei Tualang Raso masih terlihat pasif pada Pilkada Gubernur Sumatera Utara tahun 2018. Penelitian ini bertujuan untuk mengetahui bagaimana Budaya Politik Masyarakat pada saat Pilkada Gubernur Sumatera Utara tahun 2018 dan faktor apa saja yang menjadi penyebabnya Sumatera Utara dari 2018. Teori yang digunakan dalam penelitian ini adalah teori Budaya Politik dan Perilaku Golput.Penelitian ini adalah penelitian eksplanatif kuantitatif.Jumlah sampel dalam penelitian ini adalah 99 orang yang dipilih dengan menggunakanpengambilan sampel tidak disengajaKarena terkait dengan pendapatan yang didapat oleh masyarakat membuat masyarakat lebih aktif dalam bekerja pada saat pemilihan yang memperoleh hasil untuk diri sendiri sehingga merusak budaya Politik Masyarakat Kecamatan Sei Tualang Raso. Budaya politik masyarakat Kecamatan Sei Tualang Raso tergolong dalam Budaya Politik Subjek / kaula yaitu: memiliki pengetahuan dalam bidang politik yang memadai, partisipasi politik minimal dan kesadaran dalam berpolitik rendah khusus Pilkada.Kata kunci: Golongan Putih, Budaya Politik, Faktor Penyebab Golongan PutihAbstractSei Tualang Raso Subdistrict has a higher level of white compared to other sub-districts of 44.5%. Sei Tualang Raso Subdistrict community has a fairly high education and sufficient political knowledge. This should be able to prove a significant participation rate on increasing participation through mindset. But the fact that the community of Sei Tualang Raso subdistrict still looks passive at the governor of North Sumatra in 2018. This study aims to find out how the political culture of the people at the governor of North Sumatera in 2018 and what factors caused the high number of the White group in the governor of North Sumatera from 2018. The theory used in this study is the theory of political culture and Golput behavior. This research is quantitative expreslanative research. The number of samples in this study was 99 people who were elected using accidental sampling. Data collection techniques are conducted through surveys using questionnaires. Data was analyzed using a simple linear regression test with the help of SPSS version 20. Hypothesis test Results There is a value of Thitung 34.223 while the value of 1.984 in the level of significance is 5%. This means the community's political culture has a positive effect on the contributing factors of community Golput in the elections. The results of this study showed that the causal factor of the community Golput of the district of Sei Tualang Raso is the most influential political factor. Seeing that Golput's behavior emerged as a result of unbelief of voters against the government and the job factors, because with the least income gained by the public made the community more active in working at the time of the elections is considered to be the result of self-destructive political culture of the community of Sei Tualang Raso subdistrict. The political culture of the community of Sei Tualang Raso is classified as political culture subject/Kaula namely: have knowledge in the field of politics, minimal political participation and awareness in low politics, especially the elections.Kata kunci : putih, budaya politik, faktor putih